The Ortigas Center Transit Exchange public spaces regeneration through pedestrian-oriented development of Ortigas Center - Valdellon, Always S. (College of Architecture, University of the Philippines Diliman, 2018)
Public life is essential in urban centers as this determines the livability of the places we ive in. Having a good public life in urban centers provides people with safe, lively, sustainable, attractive and healthy city. Public spaces must be designed to support the needs to sustain public life. However, due to lack of priorities in providing public spaces in urban centers, pedestrians are faced with urban issues such as traffic congestion, lack of quality pedestrian expereince, fragmented urban fabric, degradation of urban environment, poor urban mobility, and lack of recreational opportunities. Thus, there is a need for public spaces regeneration. One of the important public spaces needed to be regenerated are those spaces that are attached or where pedestrians meet the transport nodes. The Ortigas Center Transit Exchange will become a hub for the improvement and strengthening of the interaction of public life and public spaces. This development will feature an Elevated Promenade and the Ortigas Center Transit Exhange provided with spaces for health, wellness and active leisure.